Proposals for Second Five Year Plan Veterinary and Animal Husbandry Department Government of Madhya Bharat - Planning Commission (Planning Commission, 1955)
The scope of development of this wing is largest than any other single industry; as the position with which we started before five years was most discouraging. Being in proud, possession of 1/3rd of the entire cattle population of the world we are most deficient in milk and its products. As against only 3 bullocks required to do an amount of work in Egypt we require 22 for the same. The development of such a grossly underdeveloped and neglected industry therefore is indispensable in case we aim to develop Land or Nation.
Government of Madhya Bharat